Selection of High-Oil Mother Plants of Noble Laurel (Laurus nobilis L.) Across Georgia - Kopaliani Lia; Kapanadze Shorena; Kipiani Nino; Arveladze Ekaterina; Jincharadze Natalia (Theoretical Hypotheses and Empirical Results, 2025)
This study presents the selection of high-oil forms of noble laurel (Laurus nobilis L.) across different regions of Georgia using the Ginzberg micromethod and microscopic analysis. The research aims to determine the optimal parameters for extracting essential oil from selected raw materials and proposes strategies for enhancing the profitability of laurel cultivation without expanding plantation areas. The introduction of high-oil laurel varieties in the subtropical regions of Georgia is expected to yield substantial economic benefits, improve local environmental conditions, mitigate soil erosion, and provide sustainable employment opportunities for rural populations.